Home energy management system - Lau, Thomas Yew Jie (2019)
In this report, the focus is developing the Home Energy Management System. The system was tested with Smart Home Controller and Smart Home Devices with web application (namely EmonPi, EmonCMS). The energy consumption plot for the household is being analyzed and illustrated using NI LabVIEW 2016 (64-bit). Using EmonCMS, the real-time data log for power consumption can be downloaded in a .csv file. The .csv file will be opened in LabVIEW GUI for analysis purposes. HEMS LabVIEW GUI is capable of optimizing energy usage by adopting Demand Side Management technique that helps to reduce energy consumption, reduce cost and also to save environment due to the reduction in carbon emission. It is also advantageous for the supplier, as consumers’ load pattern changes and the resources can be better utilized. HEMS is structured with tariff rate that varies with different times of the day. The HEMS LabVIEW GUI has 5 different modes that allow consumers to observe, manage, analyze and optimize the energy consumption. In addition, there is also solar panel and battery system developed in this HEMS LabVIEW GUI.